The STM bias voltage-dependent polymorphism of a binary supramolecular network - Cometto, Fernando Pablo (2017)
A Scanning Tunneling Microscope (STM) is used to induce a reversible transition between different polymorphs in a binary supramolecular network at the liquid/solid interface. The transition is driven externally by switching the polarity of the sample by positive or negative sample bias potentials. We demonstrate that by mixing bias-sensitive and non-sensitive molecules, we gain access to a variety of binary porous structures that can be prepared and reliably actuated for each relative concentration.